Strategies in the synthesis of dibenzo[b,f]heteropines - Maier, David Irving Hermann; Bezuidenhoudt, Barend Christiaan Buurman; Marais, Charlene (Beilstein Journal of Organic Chemistry, 2023)
The dibenzo[b,f]azepine skeleton is important in the pharmaceutical industry, not only in terms of existing commercial antidepressants, anxiolytics and anticonvulsants, but also in reengineering for other applications. More recently, the potential of the dibenzo[b,f]azepine moiety in organic light emitting diodes and dye-sensitized solar cell dyes has been recognised, while catalysts and molecular organic frameworks with dibenzo[b,f]azepine derived ligands have also been reported. This review provides a brief overview of the different synthetic strategies to dibenzo[b,f]azepines and other dibenzo[b,f]heteropines.
Keywords: dibenzo[b,f]azepine; dibenzo[b,f]heteropine; dibenzo[b,f]oxepine; iminostilbene; synthesis